The Effect of Open Ended Approach on Problem Solving Ability and Learning Independence in Students' Mathematics Lessons - Nur Alfiani Hafidzah; Zainal Azis; Irvan Irvan (UMSU, 2021)
The purpose of this study is to investigate whether 1) solving mathematical problems between students who take learning with an open-ended learning approach and students who take learning without an open-ended learning approach; 2) the influence of mathematical ability among students who have learning independence high, medium and low; 3) whether the Open-Ended learning approaches and student learning independence there was an interaction of the students' mathematical problem solving ability. This research was Quasi Experimental design The Non-equivalent Post-test Only Control Group Design. This study population throughout the first semester of seventh grade students of MTs Negeri 1 Bandar Rice academic year 2018/2019. A research technique used is purposive sampling with a sample class as a class VII-1 and VII-2 experiment as a control group. The research instrument used was a test description to measure students 'mathematical problem solving and a questionnaire to measure students' learning independence. Analysis of the data in this study is a two-way ANOVA. The results of data analysis 1) there is a mathematical problem solving among students who take the learning with the Open-Ended learning approach with students who take the lesson without learning approach Open-Ended; 2) there is an influence on the ability of mathematical problems between students who have high, medium and low learning independence; 3) there is no interaction between the Open-Ended learning approach and students 'learning independence on students' mathematical problem solving ability.